2023
DOI: 10.1109/tcomm.2023.3234995
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of RIS-Aided DCSK-WPC System With Energy Buffer

Abstract: In this paper, we propose a simultaneous transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) and energy buffer aided multiple-input single-output (MISO) simultaneous wireless information and power transfer (SWIPT) nonorthogonal multiple access (NOMA) system, which consists of a STAR-RIS, an access point (AP), and reflection users and transmission users with energy buffers. In the proposed system, the multi-antenna AP can transmit information and energy to several single-antenna reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…is the polarization of the l symbol. The d 2 l n ,l s is obtained from (11) when ∆ε = 0 [8]. The closed expression is then calculated for each of these three components.…”
Section: Closed Expression Over Multipath Rayleigh Fading Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…is the polarization of the l symbol. The d 2 l n ,l s is obtained from (11) when ∆ε = 0 [8]. The closed expression is then calculated for each of these three components.…”
Section: Closed Expression Over Multipath Rayleigh Fading Channelsmentioning
confidence: 99%
“…The scheme utilizes the advantages of MDCSK, such as low cost, less complexity, little power, and excellent anti-interference capabilities over multi-path fading channels [ 9 , 10 ]. Moreover, it only requires a simple non-coherent demodulator without channel estimation and equalization [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [15], a RIS aided wirelesspowered sensor network was studied, where the RIS is deployed to enhance the sum throughput by intelligently adjusting the phase shift of each reflecting element. In [16], an energy buffer and RIS aided WPC system was proposed to improve the error performance. In [17], it was revealed that the doubly near-far issue in MIMO WPCN can be solved effectively with a rigorous deployment of the RIS.…”
Section: Introductionmentioning
confidence: 99%